Targeting Abdominal Aortic Aneurysms with Multipotent Mesenchymal Stromal/Stem Cells: Insights into Immunological Effects - Seyed Mohammad Sajjadi; Fahimeh Lavi Arab (Current Stem Cell Research & Therapy, 2026)
Abstract: An abdominal aortic aneurysm (AAA) is a serious vascular disease characterized by progressive dilation of the abdominal aorta, resulting in an increased risk of rupture. AAA develops through multiple pathogenic mechanisms, including chronic inflammation, extracellular matrix (ECM) degradation, oxidative stress, and vascular smooth muscle cell (VSMC) apoptosis. Surgical intervention is the primary treatment for AAA; however, no effective pharmacological therapies are currently available to halt or reverse disease progression. This review evaluates the therapeutic potential of multipotent mesenchymal stromal/stem cells (MSCs) for AAA, with particular emphasis on their immunomodulatory and regenerative properties. Preclinical studies suggest that MSCs can attenuate AAA progression in animal models by modulating the inflammatory microenvironment, reducing matrix metalloproteinase activity, and promoting tissue repair. In addition, interactions between MSCs and various immune cells decrease inflammatory responses, thereby positively impacting the structure of the aortic wall. Collectively, the available evidence highlights the broad therapeutic potential of MSCs in modulating key molecular and cellular pathways involved in AAA progression. Given their ability to modulate the immune system and promote vascular regeneration, MSCs may have significant potential for developing disease-modifying therapies for AAA. By targeting key pathogenic processes involved in AAA progression, MSCs offer the potential to complement existing surgical management and address mechanisms that are not targeted by current therapies. However, additional well-designed laboratory-based and clinical studies are needed to optimize MSC-based therapeutic strategies and to establish their long-term efficacy and safety before clinical translation.